2021
DOI: 10.3390/cancers13225701
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System as a Pharmacological Target for New Cancer Therapies

Abstract: Despite the long history of cannabinoid use for medicinal and ritual purposes, an endogenous system of cannabinoid-controlled receptors, as well as their ligands and the enzymes that synthesise and degrade them, was only discovered in the 1990s. Since then, the endocannabinoid system has attracted widespread scientific interest regarding new pharmacological targets in cancer treatment among other reasons. Meanwhile, extensive preclinical studies have shown that cannabinoids have an inhibitory effect on tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 173 publications
(309 reference statements)
0
14
0
2
Order By: Relevance
“…A number of different cannabinoids have shown antitumour effects in many preclinical studies when applied individually (for review see [1,2]). In the present study, the combination of THC and CBD showed a synergistic inhibitory effect on the viability of human glioblastoma cells at 5 µM each, and can therefore be considered as a promising add-on therapy for glioblastoma, which is in agreement with the studies of other authors [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of different cannabinoids have shown antitumour effects in many preclinical studies when applied individually (for review see [1,2]). In the present study, the combination of THC and CBD showed a synergistic inhibitory effect on the viability of human glioblastoma cells at 5 µM each, and can therefore be considered as a promising add-on therapy for glioblastoma, which is in agreement with the studies of other authors [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, a growth inhibitory effect on glioma xenografts was confirmed for the selective cannabinoid receptor CB 2 agonist JWH-133 [5]. In the meantime, cannabinoid-mediated anticancer effects have also been demonstrated in a variety of other tumour entities, whereby the effects shown here range from the initially demonstrated inhibition of proliferation and induction of tumour cell apoptosis to proautophagic, anti-angiogenic, anti-invasive and antimetastatic effects (for review see [1,2]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the latter study included only 21 patients. Interestingly, there are several other studies currently listed in the U.S. National Library of Medicine’s registry on the website that addressed the systemic effects of cannabinoids in cancer patients (for a review, see [ 131 ]). However, none of the registered studies focused on cannabinoids as a potential option for the systemic treatment of skin cancer.…”
Section: Clinical Trials On Cannabinoid Use In Cancer Patientsmentioning
confidence: 99%
“…The use of molecules interfering with endocannabinoid-metabolising enzymes represents an intriguing additional therapeutic strategy. A recent review summarised the relevant preclinical studies with FAAH and MAGL inhibitors in cancer [ 107 ]. This field of investigation is still in its infancy and more studies are required to explore fully the potential of interfering with enzymes responsible for endocannabinoids’ metabolism in cancer settings.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%